Mechanical properties of graphene oxide reinforced aluminium matrix composites. (15th July 2018) - Dasari, Bhagya Lakshmi; Morshed, Muhammad; Nouri, Jamshid M.; Brabazon, Dermot; Naher, Sumsun
Abstract: In this paper, the properties of powder metallurgy produced samples of GO reinforced aluminium composites were examined. Discs of 20 mm diameter and 0.5 mm thickness were made from pure Al powder of 35 μm particle size and with GO reinforcement at different GO wt% (0.05, 0.1 and 0.2). The mixture of Al/GO powders prepared through liquid infiltration were cold compacted and then sintered. The GO reinforced Al matrix composites were characterised using the scanning electron microscope with energy dispersion spectroscopy (SEM/EDX) for investigation of the homogeneous dispersion of GO into the matrix. X-ray diffraction (XRD) analysis for crystallographic phase and micro-Raman spectroscopy was used to identify the phases inside the composite matrix after the sintering process. Micro hardness and the strength values from the produced Al/GO composites were recorded. It is evident from the results obtained that where uniform mixing is achieved, GO reinforced Al composites can be produced with similar hardness values as for those produced from rGO reinforced Al composites.